Pengaruh perlakuan refugia dan jarak tanam kedelai terhadap keragaman musuh alami - Emerensiana Uge; Kurnia Paramita Sari; Eriyanto Yusnawan; Alfi Inayati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Soybean cultivation is inseparable from the attack of plant pests. Control of soybean pests, which generally use synthetic pesticides, negatively impacts food products, environmental health, and ecosystem sustainability. Planting flowering plants around bunds can be useful in increasing the diversity of natural enemies because they can attract and serve as microhabitats for natural enemies. This research to obtain the effect of refugia treatment and soybean spacing on the diversity of natural enemies in soybean plantations. Methods: The study was designed in randomized block design, consisting of refugia and non-refugia treatments and plant spacing of 40 cm x 25 cm (J1) and 50 cm x 25 cm (J2), which was repeated three times. Sampling was carried out in the vegetative and generative phases, using yellow traps and pitfalls installed in the field for 24 hours. Results: The results showed that the most trapped natural enemy families were in the refugia treatment. The total number of trapped natural enemies was highest in the vegetative and generative phases, namely in the refugia and 2 spacing treatments (R-J2). The family of Braconidae order Hymenoptera and the group of parasitoids had the highest numbers in the refugia and non-refugia treatments. The value of the Diversity Index (H') in the refugia treatment and both plant spacings in the two growth phases was moderate, while in the non-refugia treatment, the two plant spacings and both growth phases were small and medium. Generally, the evenness index (D) value for all treatments is known to be small and medium. Conclusion: Refugia treatment and plant spacing affect the number of natural enemy populations, which is expected to suppress the development of pests in soybean cultivation.